2023
DOI: 10.1021/acsenergylett.3c01226
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Intrinsic Activity and Selectivity of Cu for Nitrate Electroreduction

Abstract: Cu-based catalysts have been widely explored for the electrochemical nitrate reduction reaction (NO3RR), while the intrinsic activity and selectivity of Cu metal for the NO3RR remain ambiguous, preventing a genuine comparison of the NO3RR performance. Here we use polycrystalline Cu foils for benchmarking and elucidate the impact of often overlooked factors on the NO3RR, including Cu facet exposure, nitrate concentration, and electrode surface area. An electropolished Cu foil exhibits a higher activity and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The FE of ammonia on 1T‐MoS 2 still stays above 80 % within the higher NO 3 − concentration and shows an arresting advantage compared to 2H‐MoS 2 (Figure S16). Thus, 1T‐MoS 2 has excellent compatibility for nitrate electroreduction over a wide range of nitrate concentrations from 0.01 to 1 M. The good concentration compatibility is useful for multiple scenarios of nitrate reduction and can be considered for the future material screening, such as a recently reported Cu‐based material [25] . To ensure the accuracy of the quantification results, 1 H nuclear magnetic resonance ( 1 H NMR ) was used to determine the ammonia concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The FE of ammonia on 1T‐MoS 2 still stays above 80 % within the higher NO 3 − concentration and shows an arresting advantage compared to 2H‐MoS 2 (Figure S16). Thus, 1T‐MoS 2 has excellent compatibility for nitrate electroreduction over a wide range of nitrate concentrations from 0.01 to 1 M. The good concentration compatibility is useful for multiple scenarios of nitrate reduction and can be considered for the future material screening, such as a recently reported Cu‐based material [25] . To ensure the accuracy of the quantification results, 1 H nuclear magnetic resonance ( 1 H NMR ) was used to determine the ammonia concentration.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure e, the double-layer charging current was plotted against the CV scan rate for the two electrodes, and the slope of linear regression lines gave a double-layer capacitance of 1.32 and 7.28 mF for the Cu foam and CuNW-15 electrodes, respectively. Therefore, the ECSA of the CuNW-15 electrode is around 5.5 times that of the Cu foam, which directly contributed to the higher current density and NO 3 RR activity . However, this may not account for the large improvement of the NH 3 selectivity (Figure d) yet, so we further examined the surface structure and exposed facets of the two electrodes using the electrosorption of hydroxide .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the ECSA of the CuNW-15 electrode is around 5.5 times that of the Cu foam, which directly contributed to the higher current density and NO 3 RR activity. 43 However, this may not account for the large improvement of the NH 3 selectivity (Figure 4d) yet, so we further examined the surface structure and exposed facets of the two electrodes using the electrosorption of hydroxide. 28 As shown in Figure 4f, the CV curve recorded on the Cu foam showed no apparent features of surface facets, similar to that of Cu foil surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…15 Numerous studies have demonstrated that the introduction of Cu metal is beneficial in accelerating the conversion of NO 3 − to NO 2 − . 27–29 The production of H 2 is always undesirable, however, in terms of the course of the reaction, reactive hydrogen (*H) is essential in the successive hydrogenation steps leading to the formation of NH 3 , and particular care should be taken to maintain a balance between the supply and consumption of *H. An insufficient supply of *H will slow down the rate of ammonia production, while an excess supply of *H will lead to severe dimerization of hydrogen atoms to form H 2 . 30 NO 3 − + e − → *NO 3 2− *NO 3 2− + e − + 2H + → *NO 2 − + H 2 O*NO 2 − + e − → *NO 2 2− *NO 2 2− + 2H + → *NO + H 2 O*NO is a key intermediate that determines the production of nitrogen or ammonia.…”
Section: Reaction Pathways Of the No3rrmentioning
confidence: 99%